2007
DOI: 10.1007/s10593-007-0126-6
|View full text |Cite
|
Sign up to set email alerts
|

Regioselectivity of the monohalogenation of 4-allyl-3-allylamino-1,2,4-triazole-5-thione

Abstract: The development of methods of obtaining new condensed heterocyclic compounds from 1,2,4-triazolethiones is an urgent problem, since these compounds possess a broad spectrum of physiological activity as analgetic, vasodilating, anti-inflammatory, and bactericidal agents and show tranquilizing action [1-3]; they are used as highly effective additives to photomaterial [4], and also are inhibitors of corrosion of nonferrous metals and alloys based on them [5].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…The bromine atoms occupy a mutual +sc-conformation to one another (torsional angle Br(1)-C(10)-C(11)-Br (2) Hence the bromination of the N-allylisatin 1 at room temperature in glacial acetic acid occurs exclusively via a classical addition of halogen to the double bond. Bearing in mind that the course of a similar reaction is sometimes significantly affected by the solvent and temperature used [18,19] we additionally carried out this synthesis in carbon tetrachloride at -20ºC. However, in this case only compound 4 was formed.…”
Section: _______mentioning
confidence: 99%
See 1 more Smart Citation
“…The bromine atoms occupy a mutual +sc-conformation to one another (torsional angle Br(1)-C(10)-C(11)-Br (2) Hence the bromination of the N-allylisatin 1 at room temperature in glacial acetic acid occurs exclusively via a classical addition of halogen to the double bond. Bearing in mind that the course of a similar reaction is sometimes significantly affected by the solvent and temperature used [18,19] we additionally carried out this synthesis in carbon tetrachloride at -20ºC. However, in this case only compound 4 was formed.…”
Section: _______mentioning
confidence: 99%
“…In particular, it is well known that successful halocyclizations can accompany the formation of heterocyclic systems of this type, i.e. those containing five-membered rings mutually annelated [2,[18][19][20][21][22][23][24]. On the other hand, it turns out that not each six-membered 1-N-allyl-substituted Alk _______ *We have shown that the reaction of 1-allyl-3-(2-hydroxyethyl)-1H-quinazoline-2,4-dione with molecular bromine in glacial acetic acid also occurs with addition of the halogen to the allyl double bond, i.e.…”
Section: _______mentioning
confidence: 99%
“…Following this logic, dihydrothiazoles should be formed most easily and this is, in fact, confirmed in numerous experiments [8][9][10]. However, in that regard, quite ambiguous information is sometimes encountered in the literature.…”
mentioning
confidence: 77%
“…5-Substituted 4-allyl-1,2,4-triazole-3-thiones react with bromine to give a fused five-membered ring [1,2]. We have used 1 H NMR spectroscopy to show that the bromination of 4-allyl-5-methyl-1,2,4-triazole-3-thione (1) in acetic acid proceeds with formation of a 10:1 mixture of 6-bromomethyl-3-methyl-5,6-dihydro-1H-[1,3]thiazolo[2,3-c][1,2,4]triazolium bromide (2) and 6-bromo-3-methyl-6,7-dihydro-1H,5H-[1,2,4]triazolo [3,4-b][1,3]thiazinium bromide (3).…”
Section: New Example Of a Dihydrothiazinementioning
confidence: 99%